A comparative analysis of methods for mapping groundwater pollution hazard: application to the Gallocanta Hydrogeologic Unit (Spain) - José María Orellana Macías (Asociación Española de Geografía, 2020)
Anthropogenic activities are the main sources of groundwater pollution. In order to prevent groundwater degradation and to apply suitable mitigation measures, hazard maps are a useful instrument for decision makers. The ultimate goal of the research is to analyse the effectiveness of several groundwater hazard indexes at the Gallocanta Lagoon Basin. To do so, the Hazard Index, the Danger of Contamination Index and the Pollutant Origin and its Surcharge Hydraulically method were applied and compare, and the potentialities and weaknesses of the resulting maps have been analysed. Accurate hazard maps were obtained and, based on their methodological approach, significant differences were found in relation to the rating process, the inventory of the sources, and the treatment of quantity and likelihood. In the light of the results, the indexes tended to undervalue the hazard level of agricultural activities, which were the main sources of pollution of the study area. Therefore, due to the characteristic land uses of the study area, typical of the Mediterranean context, some proposals to improve the indexes have been suggested.